EVALUASI PROGRAM KELUARGA HARAPAN (PKH) OLEH DINAS SOSIAL DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2018 - Yuyun Yunita; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Poverty is a serious problem experienced by some countries in the world. One of the efforts made by the Indonesian government in achieving the country's goals is a program that can prosper the community, and one of the programs made by the Indonesian government is the Family Hope Program (PKH). The Family Hope Program (PKH) has a goal, namely to reduce poverty and existing gaps. but in 2018 in Pekanbaru City, Tenayan Raya was the largest recipient of PKH assistance, the distribution of social assistance funds in Pekanbaru City faced obstacles, there were still those who had not received it, obstacles that arose, among others, invalid PKH data, savings books and ATMs that had not been distributed, lost participant card but has been replaced for a long time. This distribution system is an important part of the evaluation of the family of hope program.               This study aims to describe 1). To find out the Evaluation of the Family Hope Program (PKH) by the Pekanbaru City Social Service in 2018 and 2). Factors that hinder the Evaluation of the Family Hope Program (PKH) by the Pekanbaru City Social Service in 2018. The method in this study uses a descriptive qualitative approach. The location of the research was carried out at the Social Service and Tenayan Raya District, Pekanbaru City. Data collection techniques used are interviews and documentation. The data analysis technique used is an interactive model.               The results of the study concluded that based on the observations and analysis of the researchers were 1). Evaluation of the Family Hope Program by the Social Service in Tenayan Raya District provides an assessment of success for implementation based on an evaluation of the results. 2). Factors that hinder the Evaluation of the Family Hope Program (PKH) by the Social Service in Tenayan Raya Sub-district, Pekanbaru City, namely the lack of understanding of assistants on tasks, data differences between the Ministry of Social Affairs and the central bank which makes PKH social assistance recipients still not receiving assistance, Lack of participation of beneficiaries social services to PKH education. Keywords: Program Evaluation, Poverty, Social Assistance.